2018
DOI: 10.3389/fphar.2018.00449
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Teneligliptin in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Teneligliptin is a 3rd-generation dipeptidyl peptidase-4 (DPP-4) inhibitor. There is a limited evidence regarding the effect of teneligliptin. Therefore, this study is to assess the efficacy and safety of teneligliptin in type 2 diabetes mellitus (T2DM) patients with inadequately glycemic controlled.Methods: A search of PubMed, Medline, Embase, and The Cochrane Library during 2000.01–2018.03 was performed for randomized controlled trials of teneligliptin compared to placebo in patients with T2DM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Changes in HbA1c, FPG and PPG from baseline to end of the study (after 8 weeks of teneligliptin therapy) were -1.22 ± 1.12% or -13.3 ± 12.2 mmol/mol (p = 0.001), -35.8 ± 25.5 mg/dL or -1.99 ± 1.42 mmol/L (p = 0.001) and -60.7 ± 28.6 mg/dL or -3.37 ± 1.59 mmol/L (p = 0.001), respectively. The effectiveness of teneligliptin was also highlighted by Li et al [15] in a systematic meta-analysis of ten randomized controlled trials (RCTs) in which teneligliptin significantly (p \ 0.00001) decreased HbA1c (0.82% or 9.0 mmol/mol), FPG (18.32 mg/dL or 1.02 mmol/L) and PPG (46.94 mg/dL or 2.61 mmol/L). These data lead to the conclusion that teneligliptin effectively improves glycaemic control and is useful in the management of hyperglycaemia in patients with T2DM.…”
Section: Discussionmentioning
confidence: 78%
“…Changes in HbA1c, FPG and PPG from baseline to end of the study (after 8 weeks of teneligliptin therapy) were -1.22 ± 1.12% or -13.3 ± 12.2 mmol/mol (p = 0.001), -35.8 ± 25.5 mg/dL or -1.99 ± 1.42 mmol/L (p = 0.001) and -60.7 ± 28.6 mg/dL or -3.37 ± 1.59 mmol/L (p = 0.001), respectively. The effectiveness of teneligliptin was also highlighted by Li et al [15] in a systematic meta-analysis of ten randomized controlled trials (RCTs) in which teneligliptin significantly (p \ 0.00001) decreased HbA1c (0.82% or 9.0 mmol/mol), FPG (18.32 mg/dL or 1.02 mmol/L) and PPG (46.94 mg/dL or 2.61 mmol/L). These data lead to the conclusion that teneligliptin effectively improves glycaemic control and is useful in the management of hyperglycaemia in patients with T2DM.…”
Section: Discussionmentioning
confidence: 78%
“…The area under the curve (AUC)0-2h values for the postprandial insulin levels significantly increased after dinner in the teneligliptin 10 mg group (P < 0.05), in comparison with the corresponding values in the placebo group, but not at other times in either group. The relative insulin concentrations were higher in the teneligliptin-treated groups because of the decreased blood glucose concentrations of the patients in these groups [9].…”
Section: Effects On Insulinmentioning
confidence: 89%
“…Although, International American Diabetes Association and local guideline recommended lifestyle management as the mainstay of treatment for T2DM; with metformin as the preferred initial oral antihyperglycemic agent in most of patients, there remains no consensus regarding which classes of agents to add as dual and triple therapy, if and when required [9][10][11]23]. Clinical trials have reported safety and efficacy of teneligliptin as DPP-4 inhibitors [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…According to one meta-analysis, there was 50% chance of hypoglycemic symptoms when DPP-4 inhibitor was added to sulfonylurea, compared with placebo added to a sulfonylurea [33]. As per one meta-analysis of teneligliptin, the use of second-line therapy used with caution due to the risk of hypoglycemia, weight gain, and lower durability of glycemic response [24]. The selection of antidiabetic medications for combination therapy depends on the patient's characteristics, efficacy of initial medicine, and cardiovascular benefit [33].…”
Section: Safety Assessmentmentioning
confidence: 99%